2021
DOI: 10.1038/s41598-021-98680-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbiota and microarthropod communities in oil contaminated sites in the European Subarctic

Abstract: The present comprehensive study aimed to estimate the aftermath of oil contamination and the efficacy of removing the upper level of polluted soil under the conditions of the extreme northern taiga of northeastern European Russia. Soil samples from three sites were studied. Two sites were contaminated with the contents of a nearby sludge collector five years prior to sampling. The highly contaminated upper soil level was removed from one of them. The other was left for self-restoration. A chemical analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 76 publications
1
3
0
1
Order By: Relevance
“…Our research indicates that the composition of microbial communities analyzed at the dominant phyla level exhibited similarities to those observed in other sites contaminated with oil [17]. Significant differences in the microbial community structure were observed between the experimental sites and the reference site (Figures 8 and 13).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our research indicates that the composition of microbial communities analyzed at the dominant phyla level exhibited similarities to those observed in other sites contaminated with oil [17]. Significant differences in the microbial community structure were observed between the experimental sites and the reference site (Figures 8 and 13).…”
Section: Discussionsupporting
confidence: 71%
“…A long-term monitoring study was carried out to analyze the effects of various bioremediation methods on the restoration of biotic and abiotic components in contaminated soil [ 10 , 16 ]. Additionally, research has begun to evaluate the microbial diversity of oil-contaminated soils using metagenomic analysis [ 17 ]. Currently, active research is being conducted on soil microbial diversity based on metagenomic analysis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, two parthenogenetic species of oribatid mites (E. mahunkai and Oppiella nova (Oudemans, 1902)) were associated with soil temperature as a variable in the DB-RDA analysis (see Supplementary Table S1 for list of species identified as asexual). Oppiella nova is a cosmopolitan species found in almost all habitats sampled and sometimes associated with disturbance (Melekhina et al, 2021), while E. mahunkai is a peatland specialist (Behan-Pelletier and Lindo, 2023). Markkula et al (2019) found that year-round warming, as with the SPRUCE experiment, had no effect on total abundance of oribatids, possibly because of contrasting effects of warming in summer versus winter seasons.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Alcanivorax is an ecologically significant hydrocarbonoclastic group of bacteria. Its members are capable of degrading alkane and other derived hydrocarbon compounds as carbon and energy sources [1]. The genus Alcanivorax comes under the family Alcanivoraceae along with the two other genera of Ketobacter [2] and Pelagibaculum [3].…”
Section: Introductionmentioning
confidence: 99%